Exploring the Key Attributes of Blockchain for Medical Data Protection: A Systematic Review - Reyes Riveros, Anderson Jhanyx (2024)
This article addresses the protection of medical data in health information systems, focusing on the growing adoption of electronic health records (EHRs). It recognises the security challenges inherent in centralised systems and advocates for the secure exchange of medical data. The methodology follows the principles of the PRISMA statement, using search engines such as SCOPUS, PUBMED and IEEE XPLORE to identify 20 relevant documents. These papers focus on key attributes of blockchain technology: access control, data privacy, data security and encryption. The results indicate that access control is the most recurring attribute, followed by data privacy, data security and encryption. The discussion highlights the practical applicability of these attributes, improving patient confidence and medical workflow efficiency. The conclusions affirm the relevance of the blockchain in medical data protection, pointing to opportunities for future research, especially in less developed healthcare settings. The study provides a comprehensive framework for healthcare professionals and developers, highlighting the need for further application and exploration of implementation strategies through specific case studies. In summary, the systematic review makes a significant contribution to the understanding and application of blockchain in the secure management of medical information globally. It highlights the importance of key attributes of blockchain in improving the security, privacy and integrity of medical data, providing a comprehensive perspective for practitioners and developers interested in this area.